MaPac2, a Transcriptional Regulator, Is Involved in Conidiation, Stress Tolerances and Pathogenicity in Metarhizium acridum - Xiaobin Hu; Baicheng Li; Yan Li; Yuxian Xia; Kai Jin (Journal of Fungi)
The Gti1/Pac2 protein family, which is highly conserved across fungi, is pivotal in processes such as fungal development, spore formation, protein export, toxin production, and virulence. Despite its importance, the precise functions of Pac2 within entomopathogenic fungi have yet to be fully understood. In our study, the MaPac2 gene from M. acridum was identified, and its functions were explored. Studying the domain of the protein showed that MaPac2 comprises 422 amino acids with a characteristic Gti1/Pac2 family domain (Pfam09729). Additionally, MaPac2 is predicted to have an N-terminal protein kinase A phosphorylation site and a potential cyclin-dependent kinase phosphorylation site, highlighting its potential regulatory roles in the fungus. Our findings indicate that the inactivation of MaPac2 resulted in faster germination of conidia and a marked reduction in conidial production. Furthermore, stress tolerance tests revealed that the absence of MaPac2 significantly bolstered the fungal resilience to UV-B radiation, heat shock, SDS exposure, and stresses induced by hyperosmotic conditions and oxidative challenges. Virulence assessments through bioassays indicated no substantial differences among the WT, MaPac2-disrupted strain, and CP strains in the topical inoculation trials. Interestingly, deletion of MaPac2 increased the fungal virulence by intrahemocoel injection. Furthermore, we found that disruption of MaPac2 impaired fungal cuticle penetration due to the diminished appressorium formation but increased the fungal growth in locust hemolymph. These findings provide further insights into the roles played by Gti1/Pac2 in insect pathogenic fungi.